In vivo measurement of breast tissues stiffness using a light aspiration device. (October 2022) - Briot, N.; Chagnon, G.; Connesson, N.; Payan, Y.
Highlights: The Vlastic device is used to measure the Young's modulus of a material composed of two layers. This study uses this device to obtain in vivo in situ Young's modulus of skin and fibroglandular breast tissue in volunteers. The results obtained will allow a study on a larger number of volunteers. Abstract: Background: This paper addresses the question of the in vivo measurement of breast tissue stiffness, which has been poorly adressed until now, except for elastography imaging which has shown promising results but which is still difficult for clinicians to use on a day-to-day basis. Estimating subject-specific tissue stiffness is indeed a critical area of research due to the development of a large number of Finite Element (FE) breast models for various medical applications. Methods: This paper proposes to use an original aspiration device, put into contact with breast surface, and to estimate tissue stiffness using an inverse analysis of the aspiration experiment. The method assumes that breast tissue is composed of a bilayered structure made of fatty and fribroglandular tissues (lower layer) superimposed with the skin (upper layer). Young moduli of both layers are therefore estimated based on repeating low intensity suction tests (<40 mbar) of breast tissues using cups of 7 different diameters. Findings: Seven volunteers were involved in this pilot study with average Young moduli of 56.3 kPa  ± 16.4 and 3.04 kPa  ± 1.17 respectively for the skin and the fatty and fibroglandular tissue. The measurements were carried out in a reasonable time scale (<60 min in total) without any discomfort perceived by the participants. These encouraging results should be confirmed in a clinical study that will include a much larger number of volunteers and patients.